(untitled) (Journal of Fiber Bioengineering and Informatics, 2014)
P system is a computing model that imitates a natural process that occurs at a cellular level where all objects evolve in a maximal parallelism and distributed manner. Recent results show that it could be used to solve some problems for less computation time. In this paper, to obtain another new application of P systems, a class of P system for the matrix multiplication with integer numbers is proposed, which provides new ideas and methods for the parallel problem solving in today's big data environment. Firstly, a P system is constructed for matrix multiplication with integer numbers, and it is proven whether it is feasible through a simple example. This is a new attempt in applications of membrane computing, which gives a more effective method to implement the operation than the existing other results.